Focus on Form Approach in Second Language Oral Production - Sa-Ngaphan, Sukanda (Thammasat Review, 2015)
Focus on form (FonF) refers to an approach which attempts to provide grammar focus. It is always done in the form of corrective feedback and only takes place in meaningful communication when learners still remain focused on meaning in the context of communicative language classroom. This paper aims at providing controversial issue of form-focused instruction, explaining strategies of focus on form, and discussing when and how to correct oral production. Keyword: Focus on form (FonF), Strategies of Focus on Form, Oral Production